Pelatihan Terapi Sensori Integrasi Bagi Orang Tua dan Guru PAUD - Ria Novianti; Febrialismanto; Defni Satria (Ilin Institute, 2020)
This PKM aims to provide information and skills for parents and early childhood education teachers so that they can carry out simple integrated sensory therapy as a form of early intervention for children or students who have problems in development and growth. This training is carried out in two phases, namely the first phase of material exposure accompanied by questions and answers and continued with the second stage of sensory integration therapy practice. In this second stage, the PkM team demonstrates the therapy and the participants practise how to do therapy with the gym ball, thorns and the board. The results of the training showed an increase in the knowledge and skills of both parents and teachers regarding sensory integration in children and how to perform simple therapies that can be immediately performed at home or school. Data analysis is done by providing pretest and posttest to participants in order to obtain a tcount of 59, 159. From these results it can be concluded that community service activities can improve the knowledge and skills of parents and early childhood education teachers in conducting sensory integration therapy so that it is expected to be able to provide treatment for young children who have growth and development problems.